IMPROVING PRE SERVICE ELEMENTARY SCHOOL TEACHERS SCIENCE PROCESS SKILLS: THE IMPLEMENTATION OF EXPERIMENT LEARNING AND THE ROLE OF SCHOOL BACKGROUND (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Science process skills are considered as one of the momentous learning goals for a pre-service education program, but since students enrolled in pre-service elementary school teachers program comes from a different educational background, we evaluated whether the implementation of experiment learning and educational background might lead to a different level of success in science process skills acquisition. Results showed that different learning methods, as well as different educational background, resulted in different science process skills improvement.
Keywords: Science learning; Experiment; Learning motivation; Science process skills